"Do I need to or do I want to?" A typology of HIV status disclosure among gay, bisexual, and other men who have sex with men. Issue 2 (13th May 2020) - Lim, Jane Mingjie; Tan, Rayner Kay Jin; Chan, Jeremiah Kah Wai
ABSTRACT: Gay, bisexual, and other men who have sex with men (GBMSM) are a key population that is disproportionately affected by HIV. However, few studies have explored how and why disclosure of HIV status occurs in this population. To understand disclosure in the context of other socioecological factors, we conducted a qualitative study among 24 self-identified HIV-positive GBMSM, aged 21 and above, and who were Singaporean residents. Analysis of participants' interviews revealed that disclosure of HIV status was not a binary event; rather, each type of disclosure held varying degrees of positive and negative ramifications. Disclosure and self-acknowledgement of HIV status at each time point also had different consequences for participants' quality of life. Suggested potential interventions include increasing training for medical professionals and public awareness surrounding issues relating to HIV. Findings from this study provide a framework to describe the complexities that accompany serostatus disclosure in a setting where there are prevalent "shame-based", negative attitudes towards HIV. As such, this framework can also be utilized in the future planning and organization of services for this target population in similar contexts.